Literature Review: Analysis of the Ecological Phenomenon of Land Subsidence in Urban Areas of Indonesia - Azraq Kesya Elgiana; Jessica Aulia; Roshyanda Eka Widiatmoko Putri; Zahira Kartika Putri Suwito (CV. Tripe Konsultan, 2026)
Land subsidence is one of the increasingly serious environmental problems in various urban areas of Indonesia. This phenomenon occurs due to a combination of natural factors and human activities, particularly excessive groundwater extraction, the burden of infrastructure development, soft soil consolidation, and changes in land use. Major cities such as Jakarta, Bekasi, Bandung, Semarang, and Surabaya experience different rates of land subsidence, with significant impacts on the environment and community life. These impacts include increased flood risk, infrastructure damage, seawater intrusion, and declining urban environmental quality. This study uses a literature review method to examine the causes, characteristics, ecological impacts, and mitigation efforts related to land subsidence in Indonesian urban areas. The findings indicate that groundwater exploitation is the dominant factor accelerating land subsidence, especially in coastal cities. Therefore, sustainable water resource management, improved piped water services, stricter development control, and adaptive spatial planning policies are needed to reduce future risks.